Preparation method and application of boron-doped Fe-MOF photocatalytic material based on LMCT effect
By doping boron elements in Fe-MOF materials and enhancing light response and carrier transmission using the LMCT effect, the problem of low light absorption and carrier transmission performance of existing Fe-MOF materials is solved, and efficient photocatalytic nitrogen fixation synthesis is achieved.
Patent Information
- Application Number
- CN202411859500.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
AI Technical Summary
The existing Fe-MOF photocatalytic materials have low light absorption and carrier transport performance, making it difficult to effectively catalyze nitrogen fixation reactions.
By doping boron elements, the photoresponse and carrier transmission capabilities of Fe-MOF materials are enhanced by the LMCT effect, and boron-doped Fe-MOF photocatalytic material based on the LMCT effect was prepared.
The performance of photocatalytic nitrogen fixation synthesis is significantly improved, the light absorption and carrier transmission capabilities of photocatalytic materials are improved, and more efficient ammonia synthesis is achieved.
Smart Images

Figure CN119633902A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic ammonia synthesis and relates to a preparation method and application of a Fe-MOF photocatalytic material. Background Art
[0002] Energy and environment have always been hot topics of common concern to all mankind. Biological nitrogen fixation is highly sensitive to the environment and has a low yield, making it difficult to meet the demand for ammonia in production and life. The current Haber-Bosch process for industrial ammonia synthesis requires high temperature and high pressure conditions, consumes a lot of energy, and produces a huge carbon footprint, which will seriously threaten energy and environmental security. There is an urgent need to find a new mild and clean method for nitrogen fixation and ammonia synthesis. Solar-driven photocatalytic technology has the advantages of mild reaction conditions, energy saving and environmental protection, and is a very promising alternative to ammonia synthesis. Fe-MOF is a photocatalytic material with organic ligands as the connecting skeleton and Fe as the metal node. It has a high specific surface area and a large number of pores, which is more suitable for the catalytic conversion reaction of gases, and it has an Fe cluster structure similar to the active site of biological nitrogenase, which is conducive to the occurrence of photocatalytic nitrogen fixation reactions. However, the light absorption and carrier transport performance of Fe-MOF materials prepared by existing methods are still relatively low. Summary of the invention
[0003] The purpose of the present invention is to solve the technical problems of low light absorption and carrier transport performance of Fe-MOF prepared by existing methods, and to provide a preparation method and application of boron-doped Fe-MOF photocatalytic material based on LMCT effect.
[0004] The preparation method of boron-doped Fe-MOF photocatalytic material based on LMCT effect is as follows:
[0005] 1. Weigh 3mmol FeCl 3 6H 2 O, 3mmol FeCl 2 ·4H 2 O, terephthalic acid and 4-carboxyphenylboronic acid, FeCl 3 6H 2 O, FeCl 2 ·4H 2 O, terephthalic acid and 4-carboxyphenylboronic acid were dissolved in a mixed solution of 50 mL of DMF and acetic acid, wherein the volume fraction of acetic acid was 10%, and the volume ratio of DMF to acetic acid was 9:1, and magnetic stirring was performed at a rotation speed of 600 rpm for 30 min to obtain a precursor solution;
[0006] 2. Pour the precursor solution into a 100 mL high-pressure reactor and place it in an oven heated to 150°C for a solvothermal reaction for 12 hours. After the reaction, cool the high-pressure reactor to room temperature. Wash the precipitate produced by the solvothermal reaction with ethanol and ultrapure water three times respectively, filter it, and then dry it at 60°C for 24 hours. Grind it into powder to obtain a boron-doped Fe-MOF photocatalytic material based on the LMCT effect.
[0007] In step 1, the molar ratio of terephthalic acid to 4-carboxyphenylboric acid is 5:1, 4:2, 3:3 or 2:4.
[0008] The boron-doped Fe-MOF photocatalysis based on the LMCT effect is used as a catalyst for photocatalytic nitrogen fixation to synthesize ammonia.
[0009] The ligand-to-metal charge transfer (LMCT) process is a typical electronic transition mode of MOF materials. The enhanced LMCT process can enhance the light response and carrier migration and transport capabilities, giving MOF materials more efficient photocatalytic activity. Doping non-metallic elements to modulate the coordination environment and electronic structure of MOF materials can enhance the LMCT process. Boron is similar in size to carbon, and its electron-deficient 2p orbital makes it easy to accommodate more photogenerated electrons, which can promote the transfer of photogenerated electrons to the metal Fe center to achieve better photocatalytic nitrogen fixation performance.
[0010] The beneficial effects of the present invention are:
[0011] (1) The present invention uses the properties of non-metallic boron to promote light response and electron transport, and uses boron-containing ligands to achieve boron doping in Fe-MOF, which effectively promotes the LMCT effect and improves the performance of photocatalytic nitrogen fixation and ammonia synthesis.
[0012] (2) The presence of boron regulates the configuration of electrons at the active site and promotes the interaction between the active site and N 2 The interaction between them enhances the rapid movement of photogenerated carriers and improves the performance of photocatalytic nitrogen fixation and ammonia synthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 X-ray diffraction (XRD) patterns of the materials obtained in Examples 1-4 and Comparative Examples of the present invention;
[0014] Figure 2 The Fourier transform infrared (FT-IR) spectra of the materials obtained in Examples 1-4 and Comparative Examples of the present invention are as follows;
[0015] Figure 3The transmission electron microscope (TEM) and element mapping spectrum of the material obtained in Example 1 of the present invention, in which a represents the TEM spectrum of the material obtained in Example 1, b represents the distribution of the B element in the material, c represents the distribution of the C element in the material, d represents the distribution of the O element in the material, and e represents the distribution of the Fe element in the material;
[0016] Figure 4 The UV-visible diffuse reflectance and bandgap width spectra of the materials obtained in Examples 1-4 of the present invention and the comparative example, wherein a represents the UV-visible diffuse reflectance spectrum and b represents the bandgap width spectrum;
[0017] Figure 5 The impedance (EIS) spectra of the materials obtained in Examples 1-4 of the present invention and the comparative example;
[0018] Figure 6 This is a comparison chart of the photocatalytic nitrogen fixation and ammonia synthesis performance of the materials obtained in Examples 1-4 of the present invention and the comparative example;
[0019] Figure 7 The material obtained in Example 1 14 N. 15 Isotope detection results of photocatalytic products under N2 atmosphere;
[0020] Figure 8 This is an in-situ x-ray photoelectron spectrum of the material obtained in Example 1 of the present invention, where a represents the XPS spectrum of O1s, b represents the XPS spectrum of B1s, and c represents the XPS spectrum of Fe 2p. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0022] Specific implementation method 1: The preparation method of the boron-doped Fe-MOF photocatalytic material based on the LMCT effect in this implementation method is as follows:
[0023] 1. Weigh 3mmol FeCl 3 6H 2 O, 3mmol FeCl 2 ·4H 2 O, terephthalic acid and 4-carboxyphenylboronic acid, FeCl 3 6H 2 O, FeCl 2 ·4H 2 O, terephthalic acid and 4-carboxyphenylboronic acid were dissolved in a mixed solution of 50 mL of DMF and acetic acid, wherein the volume fraction of acetic acid was 10%, and the volume ratio of DMF to acetic acid was 9:1, and magnetic stirring was performed at a rotation speed of 600 rpm for 30 min to obtain a precursor solution;
[0024] 2. Pour the precursor solution into a 100 mL high-pressure reactor and place it in an oven heated to 150°C for a solvothermal reaction for 12 hours. After the reaction, cool the high-pressure reactor to room temperature. Wash the precipitate produced by the solvothermal reaction with ethanol and ultrapure water three times respectively, filter it, and then dry it at 60°C for 24 hours. Grind it into powder to obtain a boron-doped Fe-MOF photocatalytic material based on the LMCT effect.
[0025] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the molar ratio of terephthalic acid and 4-carboxyphenylboronic acid in step 1 is 5:1, 4:2, 3:3 or 2:4. The rest is the same as specific embodiment 1.
[0026] Specific embodiment 3: The boron-doped Fe-MOF photocatalytic material based on the LMCT effect described in specific embodiment 1 or 2 is used as a catalyst for photocatalytic nitrogen fixation to synthesize ammonia
[0027] The following examples are used to verify the effects of the present invention:
[0028] Embodiment 1:
[0029] A method for preparing a boron-doped Fe-MOF photocatalytic material based on LMCT effect comprises the following steps:
[0030] (1) Measure 10 mL of acetic acid and place it in a 100 mL volumetric flask. Add DMF to the mark and shake thoroughly. Then measure 50 mL of the mixture and place it in a 150 mL beaker. This is referred to as Solution 1.
[0031] Weigh 3 mmol FeCl 3 6H 2 O, 3mmol FeCl 2 ·4H 2 O, 4 mmol of terephthalic acid and 2 mmol of 4-carboxyphenylboric acid were stirred continuously for 30 min at a speed of 600 rpm using a magnetic stirrer to fully dissolve them in solution 1 to obtain a precursor solution.
[0032] (2) The precursor solution obtained in step (1) was transferred to a 100 mL high-pressure reactor and placed in an oven heated to 150° C. for a solvothermal reaction for 12 h. After the reaction was completed, the high-pressure reactor was cooled to room temperature. The precipitate produced by the solvothermal reaction was collected and washed three times with ethanol and ultrapure water respectively, filtered, and then dried at 60° C. for 24 h. It was then ground into powder to obtain a boron-doped Fe-MOF photocatalytic material based on the LMCT effect (abbreviated as 2B-FM).
[0033] Embodiment 2:
[0034] The preparation method of the boron-doped Fe-MOF photocatalytic material based on the LMCT effect comprises the following steps:
[0035] (1) Measure 10 mL of acetic acid and place it in a 100 mL volumetric flask. Add DMF to the mark and shake thoroughly. Then measure 50 mL of the mixture and place it in a 150 mL beaker. This is referred to as Solution 1.
[0036] Weigh 3 mmol FeCl 3 6H 2 O, 3mmol FeCl 2 ·4H 2 O, 5 mmol of terephthalic acid and 1 mmol of 4-carboxyphenylboronic acid were stirred continuously for 30 min at a speed of 600 rpm using a magnetic stirrer to fully dissolve them in solution 1 to obtain a precursor solution.
[0037] (2) The precursor solution obtained in step (1) was transferred to a 100 mL high-pressure reactor and placed in an oven heated to 150° C. for a solvothermal reaction for 12 h. After the reaction was completed, the reactor was cooled to room temperature. The precipitate produced by the solvothermal reaction was collected and washed three times with ethanol and ultrapure water respectively, filtered and dried at 60° C. for 24 h, and then ground into powder to obtain a boron-doped Fe-MOF photocatalytic material based on the LMCT effect (abbreviated as 1B-FM).
[0038] Embodiment 3:
[0039] The preparation method of the boron-doped Fe-MOF photocatalytic material based on the LMCT effect comprises the following steps:
[0040] (1) Measure 10 mL of acetic acid and place it in a 100 mL volumetric flask. Add DMF to the mark and shake thoroughly. Then measure 50 mL of the mixture and place it in a 150 mL beaker. This is referred to as Solution 1.
[0041] Weigh 3 mmol FeCl 3 6H 2 O, 3mmol FeCl 2 ·4H 2 O, 3 mmol of terephthalic acid and 3 mmol of 4-carboxyphenylboronic acid were stirred continuously for 30 min at a speed of 600 rpm using a magnetic stirrer to fully dissolve them in solution 1 to obtain a precursor solution.
[0042] (2) The precursor solution obtained in step (1) was transferred to a 100 mL high-pressure reactor and placed in an oven heated to 150° C. for a solvothermal reaction for 12 h. After the reaction was completed, the reactor was cooled to room temperature. The precipitate produced by the solvothermal reaction was collected and washed three times with ethanol and ultrapure water respectively, filtered, and dried at 60° C. for 24 h. It was then ground into powder to obtain a boron-doped Fe-MOF photocatalytic material based on the LMCT effect (abbreviated as 3B-FM).
[0043] Embodiment 4:
[0044] The preparation method of the boron-doped Fe-MOF photocatalytic material based on the LMCT effect comprises the following steps:
[0045] (1) Measure 10 mL of acetic acid and place it in a 100 mL volumetric flask. Add DMF to the mark and shake thoroughly. Then measure 50 mL of the mixture and place it in a 150 mL beaker. This is referred to as Solution 1.
[0046] Weigh 3 mmol FeCl 3 6H 2 O, 3mmol FeCl 2 ·4H 2 O, 2 mmol of terephthalic acid and 4 mmol of 4-carboxyphenylboric acid were stirred continuously for 30 min at a speed of 600 rpm using a magnetic stirrer to fully dissolve them in solution 1 to obtain a precursor solution.
[0047] (2) The precursor solution obtained in step (1) was transferred to a 100 mL high-pressure reactor and placed in an oven heated to 150° C. for a solvothermal reaction for 12 h. After the reaction was completed, the reactor was cooled to room temperature. The precipitate produced by the solvothermal reaction was collected and washed three times with ethanol and ultrapure water respectively, filtered and dried at 60° C. for 24 h, and then ground into powder to obtain a boron-doped Fe-MOF photocatalytic material based on the LMCT effect (abbreviated as 4B-FM).
[0048] Comparative Example: A method for preparing a Fe-MOF photocatalytic material, comprising the following steps:
[0049] (1) Measure 10 mL of acetic acid and place it in a 100 mL volumetric flask. Add DMF to the mark and shake thoroughly. Then measure 50 mL of the mixture and place it in a 150 mL beaker. This is referred to as Solution 1.
[0050] Weigh 3 mmol FeCl 3 6H 2 O, 3mmol FeCl 2 ·4H 2O, 6 mmol of terephthalic acid was stirred continuously for 30 min at 600 rpm using a magnetic stirrer to fully dissolve it in solution 1.
[0051] (2) The solution obtained in step (1) was transferred to a 100 mL high-pressure reactor, and placed in an oven heated to 150° C. for a solvothermal reaction for 12 h. After the reaction was completed, the reactor was cooled to room temperature; the precipitate produced by the solvothermal reaction was collected, and washed with ethanol and ultrapure water for 3 times, respectively, and filtered, and then dried at 60° C. for 24 h, and then ground into powder to obtain a boron-doped Fe-MOF photocatalytic material (referred to as FeMOF).
[0052] Application examples:
[0053] The photocatalytic materials prepared in Examples 1-4 and Comparative Examples were used to test the photocatalytic nitrogen fixation and ammonia synthesis:
[0054] The performance evaluation test of photocatalytic nitrogen fixation and ammonia synthesis was carried out in a double-layer glass reactor with a quartz cover. The two ends of the reactor were respectively provided with an inlet and exhaust valve, and there was a sampling port in front of the reactor, which was sealed with a lid with a rubber pad. 15 mg of boron-doped Fe-MOF photocatalytic material and 23.74 mg of potassium sulfite were dispersed in a reactor containing 150 ml of water. The catalyst was first dispersed evenly by ultrasound for 30 seconds. Under dark conditions, high-purity nitrogen was blown into the reactor at a flow rate of 40 mL / min and maintained at a speed of 600 rpm. After 30 minutes, it was irradiated with a 300W xenon lamp, and 3 mL was sampled every 30 minutes and the catalyst was filtered with a 0.22 μm filter head. The ammonia in the reaction solution was determined by Nash reagent, that is, 3 mL of reaction solution was taken, 30 μL of potassium sodium tartrate and 60 μL of Nessler reagent were added, and after color development for 10 minutes, the concentration of ammonia was detected at 420 nm using a UV-visible spectrophotometer.
[0055] Figure 1 The XRD patterns of the materials obtained in Examples 1-4 and Comparative Example prove that all the materials have the physical structure of MOF.
[0056] Figure 2 The Fourier transform infrared (FT-IR) spectra of the materials obtained in Examples 1-4 and Comparative Examples are used to analyze the fine structure of the materials. For FeMOF, 556 cm -1 and 1428cm -1 The peak at 748cm can be considered as Fe-O bond. -1 The peak at 1389cm corresponds to the carbon-hydrogen bond associated with the vibration of the benzene ring structure. -1 -1667cm -1 The characteristic band between 1597cm is the vibration of carboxylic acid groups associated with iron clusters. -1and 1389cm -1 The two strong peaks at 1301 cm-1 belong to OC=O, indicating the symmetric and asymmetric stretching of the carboxylic acid group, confirming the presence of dicarboxylic acid linkers in the sample. -1 and 1370cm -1 The characteristic peak of BO bond was observed at , confirming the successful synthesis of boron-containing ligand-connected materials.
[0057] Figure 3 The transmission electron microscope (TEM) and element mapping of the material obtained in Example 1 are used to analyze the microscopic morphology and elemental composition of the material. It can be seen that 2B-FM has an ellipsoidal structure with a grain diameter of about 1 μm. The material contains not only carbon, oxygen and iron elements, but also a small amount of boron, proving that the boron-doped Fe-MOF material was successfully prepared.
[0058] Figure 4 The UV-visible diffuse reflectance and bandgap width spectra of the materials obtained in Examples 1-4 and Comparative Examples are used to analyze the absorption response performance of the materials to visible light. The orange area in the figure is the actual spectrum of sunlight. It can be seen that all materials show similar absorption in the ultraviolet region. The boron-doped Fe-MOF material shows obvious enhancement of light absorption performance in the visible light region (400-550nm), which can be attributed to the LMCT process of the boron-containing ligand to the central metal Fe.
[0059] Figure 5 The impedance (EIS) spectra of the materials obtained in Examples 1-4 and Comparative Examples are used to analyze the carrier transfer performance of the materials. It can be seen that the impedance arc diameter of the boron-doped Fe-MOF material is much smaller than that of FeMOF, among which the arc diameter of 2B-FM is the smallest, indicating that the charge transfer resistance at the interface is the smallest, which has a positive effect on charge separation and transfer.
[0060] Figure 6 The photocatalytic nitrogen fixation and ammonia synthesis performance of the materials obtained in Examples 1-4 and the comparative example and the nitrogen isotope detection spectrum. The performance evaluation of the photocatalytic nitrogen fixation and ammonia synthesis shows that the ammonia synthesis performance of the boron-doped materials is significantly improved, among which 2B-FM shows the highest ammonia synthesis efficiency of 341 μmol g -1 h -1 , which is about 1.7 times that of FeMOF. In addition, the same photocatalytic reaction was carried out under Ar atmosphere, and no ammonia was detected in the system, indicating that the ammonia produced by the photocatalytic system comes from nitrogen. 14 N and 15 N Two isotopes of N 2 Photocatalytic reaction is carried out and the product can be clearly detected 14 NH 4+ triplet splitting of the signal, and 15 NH 4 + The two symmetrical split peaks of confirm that the synthetic ammonia does come from the fixed conversion of nitrogen rather than from other nitrogen-containing impurities.
[0061] Figure 7 The in-situ X-ray photoelectron spectrum of the material obtained in Example 1 is used to explore the electron transfer during the illumination process. It can be observed that under Ar atmosphere, the characteristic peak of Fe obviously moves toward the low binding energy direction, while the characteristic peaks of B and O move toward the high binding energy direction. This indicates that electrons migrate from B and O atoms in the ligand (especially from B atoms) to Fe atoms. These results show that the 2B-FM material undergoes LMCT under light irradiation. Compared with Ar atmosphere, N 2 The characteristic peak of Fe under the atmosphere has a slight positive shift. This indicates that Fe may serve as a reaction site with N 2 A certain degree of interaction occurs.
Claims
1. A method for preparing a boron-doped Fe-MOF photocatalytic material based on the LMCT effect, characterized in that The preparation method of the boron-doped Fe-MOF photocatalytic material based on the LMCT effect is as follows:
1. Weigh 3 mmol FeCl3·6H2O, 3 mmol FeCl2·4H2O, terephthalic acid and 4-carboxyphenylboric acid, dissolve FeCl3·6H2O, FeCl2·4H2O, terephthalic acid and 4-carboxyphenylboric acid in 50 mL of a mixed solution of DMF and acetic acid, wherein the volume fraction of acetic acid is 10%, and the volume ratio of DMF to acetic acid is 9:1, and stir magnetically at a speed of 600 rpm for 30 min to obtain a precursor solution; 2. Pour the precursor solution into a 100 mL high-pressure reactor and place it in an oven heated to 150°C for a solvothermal reaction for 12 hours. After the reaction, cool the high-pressure reactor to room temperature. Wash the precipitate produced by the solvothermal reaction with ethanol and ultrapure water three times respectively, filter it, and then dry it at 60°C for 24 hours. Grind it into powder to obtain a boron-doped Fe-MOF photocatalytic material based on the LMCT effect.
2. The method for preparing the boron-doped Fe-MOF photocatalytic material based on the LMCT effect according to claim 1, characterized in that In step 1, the molar ratio of terephthalic acid to 4-carboxyphenylboric acid is 5:1, 4:2, 3:3 or 2:
4.
3. The use of the boron-doped Fe-MOF photocatalytic material based on the LMCT effect according to claim 1, characterized in that The boron-doped Fe-MOF photocatalysis based on the LMCT effect is used as a catalyst for photocatalytic nitrogen fixation to synthesize ammonia.
Citation Information
Cited By
Photocatalyst for photocatalytic synthesis of ammonia and preparation method thereof
CN122164506A